Reaction to COVID-19, social media engagement and well-being: a mediation analysis. (2nd October 2021) - Khatri, Puja; Raina, Khushboo; Dutta, Sumedha; Pahwa, Harshleen; Kumari, Preeti
ABSTRACT: The COVID-19 pandemic has led to disruption of employee well-being; changing the work scenario across the globe. The psychological impact of this pandemic is an undeniable stressor greatly affecting employee well-being across cultures. Social media, in such a time of crisis, can provide the requisite support by filling the emotional, informational and instrumental voids. In order to explain how reactions to the COVID-19 pandemic influences an individual's employee well-being, this study first examines the relationships between pandemic reactions, social media engagement and employee well-being, and then develops a completely mediated model by fully integrating these links. The results, of structural equation modelling analyses conducted for 304 employees from Hospitality (129) and IT/ITeS sector (175) in India, offered strong support for the proposed model. We found that pandemic reactions were indirectly and positively associated with employee well-being; mediated by social media engagement. This study theoretically contributes to the employee well-being literature by revealing how social media engagement completely mediates the relationship between pandemic reactions and employee well-being. The study also offers practical implications by stressing the significant role played by social media engagement in influencing employee well-being in these testing times.